Characterization of arteriovenous malformation feeding vessels by carbon dioxide reactivity. - Massaro, A R; Young, W L; Kader, A; Ostapkovich, N; Tatemichi, T K; Stein, B M; Mohr, J P (American Journal of Neuroradiology, 1994)
PURPOSE To characterize cerebral hemodynamics in patients immediately before microsurgical resection of moderate to large arteriovenous malformations during isoflurane anesthesia. METHODS In angiographically defined arteriovenous malformation feeding and nonfeeding arteries, transcranial Doppler studies were performed in 25 surgeries on 22 patients. The mean blood flow velocity and pulsatility index were recorded in the middle, anterior, and posterior cerebral arteries. Transcranial Doppler velocities were measured at end-tidal carbon dioxide tensions (PetCO2) of about 25 and 35 mm Hg. Carbon dioxide reactivity was calculated as percentage mean blood flow velocity change per mm Hg PetCO2 change. RESULTS Patient demographic and clinical data for the arteriovenous malformation group followed the expected strata of a large arteriovenous malformation population. All patients were neurologically stable before surgery. A total of 43 feeding arteries and 55 nonfeeding arteries were studied. Compared with nonfeeders, feeders exhibited higher mean blood flow velocity (68 +/- 5 vs 31 +/- 3 cm/sec, P < 0.0001) and lower pulsatility index (0.64 +/- 0.03 vs 0.88 +/- 0.04, P < 0.001); anterior and middle cerebral artery velocities at normo- and hypocapnia were significantly higher than posterior cerebral arteries for both feeders and nonfeeders (P < 0.001). Carbon dioxide reactivity was 0.2 +/- 0.2%/mm Hg in feeders and 2.1 +/- 0.2%/mm Hg in nonfeeders, with no significant difference between arteries. In four of eight patients with lesions fed by the anterior circulation (middle cerebral artery with or without anterior cerebral artery feeders), posterior cerebral artery nonfeeders exhibited low reactivity. In 2 of 5 patients with ipsilateral posterior cerebral artery feeders, contralateral posterior cerebral artery nonfeeders exhibited impaired reactivity. CONCLUSIONS Quantitative transcranial Doppler studies are technically feasible in the operating room or interventional suite during anesthesia. Hemodynamic assessment using physiologic challenges of arteriovenous malformation feeders as well as angiographically uninvolved vessels may be useful as criteria in the assessment of malformations and arteriovenous malformation patients may exhibit abnormal vasoreactivity in distant uninvolved perfusion territories, suggesting a deranged neural control mechanism.